Madame D’Aulnoy e a autoria feminina no nascimento dos contos de fadas - Pessoa, Tamires de Oliveira (Brasil, 2023)
This bibliographical research aims to contribute to the historical recovery of Marie-Catherine Le Jumel de Beneville, better known as Madame d'Aulnoy. This author was one of the precursors of the literary genre “fairy tales”, in the 17th century, but for a long time her legacy was erased. Our corpus is formed by the author's short stories that were translated into Portuguese. The guiding problems of our research were the following: does the fact that the author is a woman affect the representation of men and women and their dominant relationships in fairy tales? The second question concerns the suitability or not of madame D’Aulnoy’s tales for children’s readers/listeners: what aspects of these tales can hinder or facilitate this suitability? The work will be divided into two sections: in the first, entitled “The representation of male and female characters and their relationships”, we will try to answer the first question. In the second section, entitled “The suitability or non-suitability of D’Aulnoy’s short stories for childhood”, we will seek to answer the second question.